Percutaneous Endoscopic Gastrostomy - Ronald J. Bridges; Lloyd R. Sutherland; Sydney Bass; Lorne M. Price (Canadian Journal of Gastroenterology, 1989)
Sixty-five patients who had endoscopic placement of a feeding tube between April 1984 and November 1987, were reviewed. Mean follow-up was 245 days (range one to 1391 days). The most common indication for gastrostomy insertion was a neurologic disorder (83%) Prophylactic antibiotic (cefoxitin) was given to 55% of patients (86% from one hospital). Minor complications (superficial wound infection, tube malfunction, ileus or localized abdominal pain) were seen in 55% of patients. Superficial wound infection, defined as local erythema and/or purulent discharge. was the most common complication ( 33%). No significant difference was found in the incidence of superficial wound infection between the group receiving prophylactic antibiotic and those who did not Major complications (gastric bleeding, aspiration, respiratory depression or abdominal abscess) occurred in 14% of patients The overall 30 day mortality was 23%. In 60% the cause of death was secondary to the underlying illness. No deaths occurred due to prolonged use of the feeding tube. Five patients (8%) regained the ability to eat resulting in tube removal. The authors’ experience suggests that percutaneous endoscopic gastrostomy (PEG). perhaps because of the patient population b associated with significant morbidity and mortality. Prophylactic antibiotics did not alter the incidence of wound infection associated with PEG However. this may be related to the use of a prophylactic antibiotic (cefoxttin) that has relatively poor coverage for Staphylococcus aureus, the most common organism cultured. Careful consideration must be given to patient selection prior to undertaking the procedure.